Segmented linear correlations between bone scan index and prostate cancer biomarkers, alkaline phosphatase, and prostate specific antigen in patients with a Gleason score ≥7 - Ebrahim Tasmeera, MBChB, Dip HIV Man FCNP(SA); Hadebe Bawinile, MBChB, FCNP (SA), MMed; Aldous Colleen, PhD; Partson Tinarwo, PhD (Biostatistics); Nozipho Nyakale, BSc, MBChB, FCNP (SA), MMed (Medicine, 2022)
Abstract. Technetium-99m methyl diphosphonate bone scintigraphy is relatively easily accessible for detecting bone metastases in prostate cancer patients. However, it is subjective and can be challenging to compare images taken at different time points. The bone scan index (BSI) is a more objective evaluation and allows for better comparison of images. Its correlation with other biomarkers of prostate cancer metastases such as prostate specific antigen (PSA) and alkaline phosphatase (ALP) is not clearly understood. This study thus aimed to compare the BSI correlation to PSA against that of BSI to ALP levels in patients with a Gleason score ≥7. A retrospective analysis of the medical records of 50 prostate cancer patients with a Gleason score of ≥7 referred for a bone scan between January 1, 2015 and December 31, 2018 was undertaken. Bone scans were interpreted visually, and using a semi-automated computer programme to quantify the BSI and its relation to PSA and ALP measurements. For the metastasis positive measurements, there was a statistically significant moderate positive overall linear correlation between BSI and PSA. For ALP and BSI, there were 2 segmented strong positive linear relationships between them. The first segment consisted of ALP < 375 IU/L and BSI >10%, where ALP and BSI were strongly and positively correlated. The other segment tended to have generally low BSI measurements (<10%) and also had a strong and positive correlation. The BSI was found to be better linearly correlated with ALP than PSA.